The Active Compounds in Polyscias Scutellaria Identified Based on the Solvent - Dwi Pratiwi Kasmara; Norhashima Abd. Rashid; Susi Amenta Beru Perangin – Angin (Indonesian Journal of Global Health Research, 2024)
Polyscias scutellaria, commonly known as bowl leaf, is a medicinal plant belonging to the Araliaceae family, renowned for its diverse therapeutic properties, particularly in Southeast Asia. The plant is traditionally used for its antioxidant, anti-inflammatory, and other health benefits, attributed to its rich array of bioactive compounds, such as phenolics, flavonoids, saponins, and alkaloids. Objective to explore the phytochemical composition and antioxidant potential of various extracts of Polyscias scutellaria to assess its pharmacological significance and therapeutic applications. The study employed qualitative and quantitative analyses to identify active compounds in Polyscias scutellaria extracts, using extraction methods including 96% ethanol, ethyl acetate, and methanol. Phytochemical screening was performed, and antioxidant activity was evaluated using the DPPH method. The phytochemical screening revealed a rich profile of bioactive compounds, including phenolics, flavonoids, saponins, and alkaloids. The 96% ethanol extract showed a phenolic content of 14.67 ± 0.33 mg GAE/g and a flavonoid content of 1.83 ± 0.05 mg QE/g, while the ethyl acetate extract exhibited the highest total phenolic content of 289.813 ± 11.381 mg GAE/g. Antioxidant activity analysis demonstrated significant scavenging effects, with the ethanol extract achieving an IC50 value of 46.28 mg/mL. The methanol extract contained higher concentrations of alkaloids, carbohydrates, and saponins, indicating potential for functional health applications. This study underscores the pharmacological significance of Polyscias scutellaria and its bioactive constituents, highlighting its potential as a natural antioxidant source and functional ingredient. Further research is warranted to validate its therapeutic efficacy and explore its applications in drug discovery and modern health practices.